2015
DOI: 10.1007/s00248-015-0669-5
|View full text |Cite
|
Sign up to set email alerts
|

Soil Parameters Drive the Structure, Diversity and Metabolic Potentials of the Bacterial Communities Across Temperate Beech Forest Soil Sequences

Abstract: Soil and climatic conditions as well as land cover and land management have been shown to strongly impact the structure and diversity of the soil bacterial communities. Here, we addressed under a same land cover the potential effect of the edaphic parameters on the soil bacterial communities, excluding potential confounding factors as climate. To do this, we characterized two natural soil sequences occurring in the Montiers experimental site. Spatially distant soil samples were collected below Fagus sylvatica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
43
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 52 publications
12
43
1
1
Order By: Relevance
“…1 ). These results are consistent with previous studies on grasslands 24 and temperate beech forests 25 . The most abundant phylotype (3.99% ± 2.44) is an uncultured member of the Subgroup 6 of the Acidobacteria .…”
Section: Resultssupporting
confidence: 94%
“…1 ). These results are consistent with previous studies on grasslands 24 and temperate beech forests 25 . The most abundant phylotype (3.99% ± 2.44) is an uncultured member of the Subgroup 6 of the Acidobacteria .…”
Section: Resultssupporting
confidence: 94%
“…This means that, notwithstanding the significant abiotic and biotic differences of the soils (Poli et al ., ), tomato roots seem to display a broadly similar expression profile when grown in native soils, as compared with roots grown in the control substrate. Soil is considered the primary force driving plant–microbiota diversity (Jeanbille et al ., ); our present data reveal that soil is also a key factor in shaping the molecular profile in tomato.…”
Section: Discussionsupporting
confidence: 61%
“…Different soil types have been shown to affect bacterial microbiomes of Fagus sylvatica roots (Nicolitch et al, 2016), although that study did not distinguish the possible influence of different ectomycorrhizal fungi. Other studies have shown effects of soil chemistry on composition of soil microbial communities including soil pH, and nutrient availability (Landesman et al, 2014;Jeanbille et al, 2016) and differences in the bioavailability of nutritive cations have been shown to impact the efficacy of mineral weathering bacterial communities (Lepleux et al, 2013). In the present study, we distinguished separate effects of soil from different horizons and of different ectomycorrhizal fungi on the bacterial microbiomes associated with P. sylvestris roots since clear differences between roots colonized by different fungi were present within the same soil horizon in unfertilized systems ( Table 2).…”
Section: Discussionmentioning
confidence: 99%